Removal of Methylene Blue Dye from Wastewater Using Periodiated Modified Nanocellulose - Hizkeal Tsade Kara; Sisay Tadesse Anshebo; Fedlu Kedir Sabir; Getachew Adam Workineh (International Journal of Chemical Engineering)
The study was focused on the preparation and characterizations of sodium periodate-modified nanocellulose (NaIO4-NC) prepared from Eichhornia crassipes for the removal of cationic methylene blue (MB) dye from wastewater (WW). A chemical method was used for the preparation of NaIO4-NC. The prepared NaIO4-NC adsorbent was characterized by using X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscope (SEM), energy-dispersive X-ray (EDX), and Brunauer–Emmett–Teller (BET) instruments. Next, it was tested to the adsorption of MB dye from WW using batch experiments. The adsorption process was performed using Langmuir and Freundlich isotherm models with maximum adsorption efficiency (qmax) of 90.91 mg·g−1 and percent color removal of 78.1% at optimum 30 mg·L−1, 60 min., 1 g, and 8 values of initial concentration, contact time, adsorbent dose, and solution pH, respectively. Pseudo-second-order (PSO) kinetic model was well fitted for the adsorption of MB dye through the chemisorption process. The adsorption process was spontaneous and feasible from the thermodynamic study because the Gibbs free energy value was negative. After adsorption, the decreased values for physicochemical parameters of WW were observed in addition to the color removal. From the regeneration study, it is possible to conclude that NaIO4-NC adsorbent was recyclable and reused as MB dye adsorption for 13 successive cycles without significant efficient loss.